Public Health in Political Dilemma - A Case for Covid-19 Control - Singh, SK; Srivastava, VK (Indian Journal of Community Health, 2020)
COVID 19 has been declared a Public Health Emergency of International Concern by the WHO (1). The management of COVID 19 pandemic by Govt. of India has been applauded by the WHO for its timely and strict actions. No doubt we have borrowed time from the lockdown but it could have been utilized in a much better way to control. The epidemiological opinion is that the harshest lockdown was acceptable but its extension was not required as we have not been able to sustain the benefits of lockdown gained in the beginning. The gain of lockdown could have been better had it been coupled with meticulous contact tracing and containment measures during the early period of pandemic. A subsequent failure to ensure all these together resulted in spread of virus everywhere in spite of lockdown. It has also given a false feeling to the public that lockdown will prevent infection.